2007
DOI: 10.1158/1078-0432.ccr-07-1083
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mRNA Expression Levels Predict for Overall Survival in Ovarian Cancer after Chemotherapy

Abstract: Purpose:We investigated whether BRCA1mRNA expression levels may represent a biomarker of survival in sporadic epithelial ovarian cancer following chemotherapy treatment. Experimental Design: The effect of loss of BRCA1 expression on chemotherapy response in ovarian cancer was measured in vitro using dose inhibition assays and AnnexinV flow cytometry. Univariate and multivariate analyses were done to evaluate the relationship between BRCA1 mRNA expression levels and survival after chemotherapy treatment in 70 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(164 citation statements)
references
References 39 publications
(48 reference statements)
6
154
1
3
Order By: Relevance
“…Although Harkin's group has shown that reduced BRCA1 expression confers increased resistance to taxanes in vitro, there was a non-significant trend in their retrospective patient analysis to suggest that patients with high tumor levels of BRCA1 may gain a survival advantage with taxane-based chemotherapy. 2 In this patient cohort, Cox proportional modeling revealed a significant correlation of low ERCC1 expression with a better OS, implying that ERCC1 may also be a relevant predictive marker in OC. Our study supports preclinical data demonstrating that inhibition of the ERCC1 protein by antisense RNA expression in A2780 and the highly resistant OC cell line OVCAR10, enhanced platinum sensitivity in vitro.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although Harkin's group has shown that reduced BRCA1 expression confers increased resistance to taxanes in vitro, there was a non-significant trend in their retrospective patient analysis to suggest that patients with high tumor levels of BRCA1 may gain a survival advantage with taxane-based chemotherapy. 2 In this patient cohort, Cox proportional modeling revealed a significant correlation of low ERCC1 expression with a better OS, implying that ERCC1 may also be a relevant predictive marker in OC. Our study supports preclinical data demonstrating that inhibition of the ERCC1 protein by antisense RNA expression in A2780 and the highly resistant OC cell line OVCAR10, enhanced platinum sensitivity in vitro.…”
Section: Discussionmentioning
confidence: 65%
“…9 A recent study of 70 patients treated with platinum-based therapy concluded that low to intermediate levels of BRCA1 mRNA were associated with improved survival compared to those with high levels. 2 However, in this study, there were heterogeneous BRCA1 levels in the high BRCA1 group and a significant number of patients were treated with an outdated chemotherapy regimen, platinum and cyclophosphamide, which may not be reflective of patients receiving current chemotherapy. Although BRCA1 deficiency is generally associated with improved prognosis after platinum-based treatment, not all reports have validated this finding, 12,13 indicating that further studies are needed.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…However, the treatment can still be viewed largely as a 'shot in the dark' and the tools available to help predict who will respond optimally to which treatment are still relatively crude. Some molecules, such as BRCA1 (Quinn et al, 2007), soluble Fas levels (Chaudhry et al, 2008), Death Receptor 4 and TNF receptor 2 (TNFR2) (Dong et al, 2008), EF24 (Selvendiran et al, 2007), and trophinin (Baba et al, 2007), have been shown to correlate with cisplatin resistance in human ovarian cancer. The molecular markers involved in the activity of chemotherapeutic agents can shed light on the successes and failures of treatment in ovarian cancer patients and can also provide a basis for individualised therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hypermethylation of the BRCA1 promoter region causes increased sensitivity to platinum drugs (Teodoridis et al 2005). Also in two ovarian cancer cell lines decreasing BRCA1 mRNA using inhibition assays correlated to increased sensitivity to platinums (Quinn et al 2007). They also show that patients with low/intermediate levels of BRCA1 mRNA have a significantly improved overall survival following platinum-based chemotherapy compared to patients with high levels of BRCA1 mRNA.…”
Section: Resistance Developmentmentioning
confidence: 99%